High Glucose Decreases Expression and Activity of p-glycoprotein in Cultured Human Retinal Pigment Epithelium Possibly through iNOS Induction - Zhang, Yuehong; Li, Chunmei; Sun, Xuerong; Kuang, Xielan; Ruan, Xiangcai (PLOS ONE, 2012)
Inhibition of p-glycoprotein under hyperglycemic conditions has been reported in various barrier tissues including blood-brain barrier, intestine, and kidney, and has been linked to significant clinical complications. However, whether this is also true for the outer blood-retinal barrier constituted by retinal pigment epithelium, or has a role in pathogenesis of diabetic retinopathy is not yet clear. In this study, using cultured human retinal pigment epithelium cell line D407, we found that high glucose exposure induced a significant decrease in p-glycoprotein expression both at mRNA and at protein levels, accompanied by an attenuated p-glycoprotein activity determined by intracellular rhodamine 123 retention. In marked contrast, the expressions of both mRNA and protein levels of inducible nitrate oxide synthase (iNOS) increased, and were accompanied by increased extracellular nitrate/nitrite production by Griess reaction. In addition, mRNA levels of nuclear receptors revealed a decreased expression of pregnane X receptor after the exposure of high glucose. However, the subsequent alterations in production of nitrate/nitrite, functional expression of p-glycoprotein, and mRNA levels of pregnane X receptor were partially blocked when pretreated with S,S′-1,3-phenylene-bis(1,2-ethanediyl)-bis-isothiourea•2HBr (PBITU), a selective iNOS inhibitor. Moreover, the effects of PBITU were antagonized with the addition of L-arginine, a substrate for NO synthesis. Our in vitro results suggest for the first time that iNOS induction plays a novel role in decreased p-glycoprotein expression and transport function at the human outer blood-retinal barrier under hyperglycemic conditions and further support the concept of inhibiting iNOS pathway as a therapeutic strategy for diabetic retinopathy.